Construction of Axially Chiral Biaryls via Atroposelective ortho-C–H Arylation of Aryl Iodides - Liu, Ze-Shui; Deng, Shuang; Gao, Qianwen; Hua, Yu; Cheng, Hong-Gang; Qi, Xiaotian; Zhou, Qianghui (ACS catalysis, 2023)
Due to the dichotomy between reactivity and stereoselectivity, the synthesis of axially chiral biaryls via enantioselective C–H arylation remains a daunting challenge. This full account describes the development of a general and modular platform for the construction of axial chirality through atroposelective ortho-C–H arylation of aryl iodides based on palladium/chiral norbornene cooperative catalysis. It is a three-component cascade process that involves readily available aryl iodides, 2,6-substituted aryl bromides, and various terminating reagents (e.g., olefins, alkynes, boronic acids, etc.) as building blocks. Key features of this method include broad functional group tolerance, high enantioselectivities, a distinct stereoinduction model, and good step economy and scalability. Notably, this method is also amenable for the synthesis of phenanthridinones with C–N axial chirality and chiral fluorenols through axial-to-axial and axial-to-central chirality transfer, respectively. Lastly, the origin of enantioselectivity in this method and the ortho-substituent effect of 2,6-substituted aryl bromides on stereoinduction are elucidated by density functional theory calculations.